2019
DOI: 10.1080/0312407x.2019.1571619
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Literature Reviews Published inAustralian Social Work(2007–2017)

Abstract: This study examined the nature of literature reviews published in Australian Social Work between 2007 and 2017. An audit was conducted to determine the number of reviews; types of reviews (systematic, meta-analysis, metasynthesis, scoping, narrative, conceptual, critical); and elements that were commonly reported (based on items drawn from the PRISMA checklist) including quality appraisal. A total of 21 reviews were identified. Results showed the overall number of reviews published remained relatively consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…We developed our framework in three steps: (1) synthesising existing approaches (Aromataris & Pearson, 2014; Aromataris et al, 2015); (2) selecting the methodological criteria (Sny-der, 2019) and (3) adjusting the criteria (Strandberg & Simpson, 2019). The full framework is presented in Table 4.…”
Section: Methodological Framework Of Literature Reviewsmentioning
confidence: 99%
“…We developed our framework in three steps: (1) synthesising existing approaches (Aromataris & Pearson, 2014; Aromataris et al, 2015); (2) selecting the methodological criteria (Sny-der, 2019) and (3) adjusting the criteria (Strandberg & Simpson, 2019). The full framework is presented in Table 4.…”
Section: Methodological Framework Of Literature Reviewsmentioning
confidence: 99%
“…This had increased to 79 per cent of papers in 2014 (Simpson & Lord, 2015). Also encouraging is the finding by Strandberg and Simpson (2020) that there were signs of a growing methodological pluralism within the journal.…”
mentioning
confidence: 89%
“…Research is an essential element of the social work profession (Orme & Shemmings, 2010). It generates knowledge to support social work practice and human services, as well as to further social justice agendas (Shaw, 2007;Strandberg & Simpson, 2020). The Australian Association of Social Workers (AASW) recognises that conducting research and using knowledge generated from research is a core practice standard (AASW, 2013).…”
mentioning
confidence: 99%
“…The study further revealed that companies' opinions of non-qualified auditors were received by companies seeking higher costs to acquire debts. Strandberg and Grahame (2020) investigated the nature of literature on audit conduct opinions of stakeholders published in Australian Social works for a period of 11 years, 2007 to 2017. The study explored a total of 21 literature reviews using exploratory review methods.…”
Section: Empirical Reviewmentioning
confidence: 99%